Volume 6B: Materials and Fabrication 2013
DOI: 10.1115/pvp2013-98039
|View full text |Cite
|
Sign up to set email alerts
|

Round Robin Prediction of Residual Stresses in the Edge-Welded Beam R6 Validation Benchmark Problem

Abstract: A simple austenitic steel beam specimen with a single autogenous weld bead laid along its top edge is an ideal training problem for novice weld modellers. This geometry may be analysed using either 3D or 2D FE models and employing either block-dumped or moving heat source techniques, with a variety of material constitutive models. This paper describes a residual stress simulation round robin performed on the validation benchmark problem of this type recently added to the R6 defect assessment procedure. A varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Despite the overall similarity it is discernible that, for vertical cutting, the cuttinginduced plastic strain associated with the isotropic hardening model is actually slightly larger than that associated with the combined hardening model. This can be attributed to the overestimation of weld residual stresses using an isotropic hardening model [25,27]. However, the effects of cyclic strain hardening may become more pronounced if extensive and significant reverse yielding occurs during cutting, but this is a topic for future work.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite the overall similarity it is discernible that, for vertical cutting, the cuttinginduced plastic strain associated with the isotropic hardening model is actually slightly larger than that associated with the combined hardening model. This can be attributed to the overestimation of weld residual stresses using an isotropic hardening model [25,27]. However, the effects of cyclic strain hardening may become more pronounced if extensive and significant reverse yielding occurs during cutting, but this is a topic for future work.…”
Section: Discussionmentioning
confidence: 99%
“…Combined hardening models have been shown to be best suited to describing the cyclic plastic behaviour of austenitic Type 316 stainless steel [25,26]. It has been also demonstrated that the use of combined hardening models and moving heat sources can most accurately capture the residual stresses in stainless steel welds [22,23,25,[27][28][29].…”
Section: Macrographmentioning
confidence: 99%
See 3 more Smart Citations